O problema de Dirichlet para a equação da hipersuperfícies mínimas em domínios limitados - Nascimento, Antonio Carlos do (2014)
In this work we study the classical results of existence and non-existence of solutions for the Dirichlet problem for the minimal hypersurfaces equation in bounded domains of Rn due to Jenkins-Serrin [8].